A Comparative Study of Filial Piety Education in Chinese and Malaysian Chinese - Yanfang Wang; Muhammad Daoh; Nur Muneerah Kasim (Research Synergy Foundation, 2025)
Filial piety, a fundamental Confucian value, is traditionally emphasized in Chinese education. However, globalization and modernization have influenced how filial piety is taught and perceived. This study explores the similarities and differences in filial piety attitudes among Chinese and Malaysian Chinese university students. The sample consists of 598 students, including 325 from China and 273 from Malaysia, selected through stratified random sampling from major universities. Independent sample t-tests were conducted using SPSS to analyze the responses. The statistical analysis indicates that while there are shared perspectives, differences also exist in filial piety attitudes between the two groups. Both Chinese and Malaysian Chinese college students highly value the culture of filial piety. In the dimension of authority, the mean scores of both groups are relatively low and similar, suggesting that under the influence of modern society, traditional notions of authority have weakened among university students in both countries. Chinese university students demonstrate more proactive emotional respect, whereas Malaysian Chinese students place greater emphasis on traditional commemorative rituals. Additionally, interviews with 11 education experts (six from China and five from Malaysia) yielded recommendations and strategies to strengthen filial piety education.